Asas-Asas Hukum Keluarga Islam - Muhammad Tsaqib Idary (JURNAL HUKUM PELITA, 2023)
This article identifies the principles of family law contained therein. From the identification results, the principles of family law were found, namely the principle of freedom, the principle of protection and prevention, the principle of monogamy, the principle of responsibility and justice and the principle of legal certainty. Legal principles are important because truth is the basis for thinking and reasoning, especially in enforcing and implementing the law. Legal principles are the most important subsystem of the legal system and legal principles. Principles take precedence over a system of rules. This is not only because legal principles are more universal, but also because they reflect cultural values and messages that should be embodied in the supremacy of law. Legal principles can be used as a basis or justification for the formation of a legal regulation, or can represent the legal relationship of legal regulations, including the values, aspirations, ideas, social or ethical views that are formed. From an Islamic perspective, principles can be formed in the order of Islamic legal philosophy. The type of research that the author uses is library research with a qualitative descriptive research approach. The conclusion of this article is that legal principles are understood as the fundamental ideas behind a legal system, which are formulated in legal regulations and judges' decisions, and are the basis for making certain regulations and decisions.